Analysis Of The Role Of Blockchain Technology In Recording Motor Vehicle Ownership Data - Santoso, Ahmad Imam; Zarlis, Muhammad; Mawengkang, Herman (Universitas Medan Area, 2024)
The importance of the role of motor vehicles in human life is revealed through its transformation from a tertiary need to a secondary one. In Indonesia, the number of motor vehicles reached 136.191 million units in 2020, prompting the government to regulate registration and identification through Presidential Regulation No. 5 of 2015. This research addresses issues related to motor vehicle administration in Indonesia, focusing on transparency, data integrity, and information availability. Inspired by the rapid growth in the number of motor vehicles and the increasing cases of theft, this research aims to design and implement an innovative motor vehicle ownership recording system using blockchain technology. This approach aims to enhance the accessibility of information on the origin and ownership of vehicles or Vehicle Registration Numbers (VRN), which is currently limited in both manual and online forms. The research methodology involves the design and implementation of blockchain technology, tested to verify its effectiveness in achieving transparency and data security goals. The research results indicate that this system can provide more comprehensive and distributed information to the general public, overcoming the limitations of centralized systems. The conclusion of this research affirms that the application of blockchain technology can be an innovative and effective solution to improve motor vehicle administration. The implications of this research include increased efficiency, security, and availability of information in handling vehicle administration, potentially having a positive impact on the general public and related industries